The ironwood tree - DiTerlizzi, Tony (DiTerlizzi, Tony. Spiderwick chronicles, 2004)
After Mallory is kidnapped at her fencing meet, Jared and Simon search for her near an old quarry and find themselves amidst dwarves and goblins.